Drug Provocation Testing as the Cornerstone for Diagnosing Antituberculosis Drug Hypersensitivity - Gautami, Gautami; Syanindita Putri Larasati, Made; Kharisma Setyawan, Moses; Suryana, Ketut (Jurnal Indonesia Sosial Sains, 2026)
Drug hypersensitivity reactions (DHRs) remain an important challenge in everyday clinical practice, especially in conditions that require prolonged multidrug treatment such as tuberculosis. Hypersensitivity to anti-tuberculosis therapy (ATT) can disrupt ongoing treatment, reduce adherence, and ultimately compromise therapeutic outcomes. For this reason, an accurate and structured diagnostic approach is crucial to identify drug-related hypersensitivity and non-immunologic adverse reactions is therefore crucial to support safe clinical decision making. A 52-year-old male patient with pulmonary tuberculosis developed recurrent hypersensitivity manifestations during the continuation phase of ATT. The patient experienced two episodes of generalized pruritus, soft tissue swelling, and dyspnea, both of which required hospitalization. Similar symptoms recurred after ATT was substituted with levofloxacin. He was subsequently referred for allergy evaluation and underwent drug provocation testing (DPT) performed as a graded drug challenge with performed sequentially with isoniazid, rifampicin, ethambutol, and pyrazinamide under close clinical supervision. No immediate reactions were observed during in-hospital monitoring. No immediate hypersensitivity reactions were observed during in-hospital monitoring; however, delayed cutaneous symptoms developed after discharge following exposure to each tested agent, supporting the diagnosis of delayed-type hypersensitivity reactions. This case underscores the clinical challenges associated with delayed hypersensitivity reactions to multiple first-line anti-tuberculosis drugs. Drug provocation testing, when applied in a controlled and risk-stratified setting, provides valuable diagnostic clarification and assists in selecting alternative therapeutic strategies. A systematic diagnostic strategy is key to guiding individualized and safe treatment decisions in tuberculosis patients with suspected drug hypersensitivity.